Pengaruh Pengetahuan Produk Halal, Religiusitas dan Halal Awareness Terhadap Keputusan Pembelian Kosmetik Halal (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis research was conducted to determine the effect of knowledge of halal products, religiosity, and halal awareness on purchasing decisions of wardah brand halal cosmetics consumers who buy wardah products at the Bagaskara Store and Bu Mun stores in Wajak sub-district, Malang Regency, East Java 65141. Methods used is explanatory research which aims to explain the position of each variable and its influence between one variable and another, and the data source used is primary data by distributing a linkert scale questionnaire to respondents who have visited or purchased Wardah products. The sample calculation in this study used the Slovin formula which resulted in 100 respondents. The results of this study were variables of knowledge of halal products, religiosity and halal awareness of purchasing decisions.Keywords: the effect of knowledge of halal products, religiosity, halal awareness and Purchasing Decision.